2014
DOI: 10.7317/pk.2014.38.6.744
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Electrospun Antibacterial Curcumin-loaded Zein Nanofibers

Abstract: Electrospinning was used to load curcumin (a natural compound that has antiinflammatory properties) into zein nanofibers. An emulsifier, Tween 80, was combined with curcumin in the zein nanofibers. The morphology of the curcumin-loaded zein nanofibers (CLZNFs) was observed using field emission scanning electron microscopy. Investigation of curcumin released from the zein nanofibers into phosphate buffer saline at pH 7 indicated that the Tween 80 had increased the amount of curcumin released from the CLZNFs. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In addition, curcumin-loaded zein nanofibers exhibited excellent antibacterial activity, and the inhibition efficiency against food-borne pathogens increased with the increase of curcumin content (75)(76)(77)(78). In addition, curcumin-loaded nanofibril films prepared by dispersing electrospun zein into konjac and glucomannan solution exhibited better hydrophobicity, water resistance property and excellent antibacterial activity, which can be used as food packaging materials (38).…”
Section: Zein-based Nanofibersmentioning
confidence: 99%
“…In addition, curcumin-loaded zein nanofibers exhibited excellent antibacterial activity, and the inhibition efficiency against food-borne pathogens increased with the increase of curcumin content (75)(76)(77)(78). In addition, curcumin-loaded nanofibril films prepared by dispersing electrospun zein into konjac and glucomannan solution exhibited better hydrophobicity, water resistance property and excellent antibacterial activity, which can be used as food packaging materials (38).…”
Section: Zein-based Nanofibersmentioning
confidence: 99%
“…Besides, encapsulation in electrospun zein NFs improved fish oil oxidative stability. Electrospun zein NFs were also used for curcumin encapsulation [71]. Curcumin (1.6 wt%) loaded zein NFs exhibited a potential to be used as an antibacterial non-woven mat owing to leading restricted growth of Staphylococcus aureus (83%).…”
Section: Encapsulation Of Food Bioactivesmentioning
confidence: 99%
“…126 Bui et al reported that nanofibers containing 1.6 wt % curcumin could efficiently inhibit growth of S. aureus (83%), suggesting their potential application as an antibacterial nonwoven mat. 127 Curcumin-loaded zein membrane was utilized for Fe 3+ sensing by naked-eye detection with an optical detection limit of 0.4 mg/L. 128 Recently, a study by Wang and co-workers demonstrated that the curcumin-loaded zein fibers possessed good antibacterial activity toward S. aureus and Escherichia coli, and the predominant release mechanism of curcumin from fibers was Fickian diffusion, suggesting their potential antimicrobial applications.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 99%
“…Brahatheeswaran and co-workers developed the smooth zein–curcumin fiber with a mean diameter of 310 nm and found that curcumin maintained its free radical scavenging activity and showed sustained release behavior . Bui et al reported that nanofibers containing 1.6 wt % curcumin could efficiently inhibit growth of S. aureus (83%), suggesting their potential application as an antibacterial nonwoven mat . Curcumin-loaded zein membrane was utilized for Fe 3+ sensing by naked-eye detection with an optical detection limit of 0.4 mg/L .…”
Section: Electrospinning Of Natural Biomaterials and Applicationsmentioning
confidence: 99%